The theme “Health of the Elderly” in Revista Brasileira Multidisciplinar: Analysis of a decade (2010 – 2020) (Research, Society and Development, 2021)
With the current changes in demographic profiles, multidisciplinary work has gained prominence with regard to the health of the elderly, understanding that comprehensive care can interfere with health outcomes, whether through prevention, treatment or reduction of injuries. The aim of this study was to investigate publications on elderly health in the Revista Brasileira Multidisciplinar, as well as to discuss possible issues related to comprehensive health care for the elderly. This is a retrospective, bibliographical and exploratory review study, carried out between May and June 2021, with a descriptive approach, in the database "Multidisciplinary Brazilian Journal" through the descriptors/key words "Health of the Elderly" "Elderly" and “Elderly”. Inclusion criteria were complete articles published in the journal between January 2010 and December 2020 identified in June 2021. Only articles that had any relationship with the health of the elderly were included. In total, 5 articles participated in the study. With regard to the authors' initial training, it was observed that the Nursing course was the one with the highest prevalence. Authors with training in Dentistry, Nutrition, Physical Education and Medicine were identified, showing that there is a consolidation process between the health of the elderly and the care provided in a multidisciplinary way. Literature review studies were found showing preventive strategies that enable a healthier aging process, delaying the development and worsening of diseases. It is concluded that multidisciplinary care presents itself as an alternative to guarantee comprehensive care.